Film coating method of electrophoresis piece
By forming a dense structure of zirconized film on the surface of the electrophoretic part, the problem of easy falling off in the prior art is solved, and the corrosion resistance and wear resistance of the electrophoretic part are significantly improved.
Patent Information
- Application Number
- CN202510202422.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-02-24
AI Technical Summary
The zirconized film formed by existing electrophoretic parts after soaking is prone to fall off, resulting in its corrosion resistance and wear resistance that cannot meet application needs.
By mixing the zirconiumizing agent, borate and complexing agent in a specific mass ratio, a zirconium-based conversion liquid is obtained, and the electrophoretic member is soaked in this liquid to form a dense structure of zirconium-based film.
The adhesion between the zirconized film and the surface of the electrophoretic part is enhanced, and the probability of the zirconized film falling off is reduced, thereby improving the corrosion resistance and wear resistance of the electrophoretic part.
Smart Images

Figure CN119710865A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrophoresis technology, and in particular to a coating method for an electrophoresis component. Background Art
[0002] Electrophoretic parts need to be surface treated before electrophoretic treatment. Generally, a zirconium film is formed on the surface of the electrophoretic parts to improve the corrosion resistance and wear resistance of the electrophoretic parts. However, in the related art, the zirconium film formed by the electrophoretic parts after immersion is easy to fall off, resulting in its corrosion resistance and wear resistance failing to meet the application requirements. Therefore, it is urgent to provide a coating method for electrophoretic parts. Summary of the invention
[0003] In response to the above technical problems, the present invention provides a coating method for an electrophoretic component, which can form a zirconium film with a dense structure on the surface of the electrophoretic component, thereby enhancing its adhesion to the surface of the electrophoretic component and reducing the probability of the zirconium film falling off, thereby improving the corrosion resistance and wear resistance of the electrophoretic component.
[0004] An embodiment of the present invention provides a coating method for an electrophoretic element, and the coating method for an electrophoretic element includes: Mixing step: mixing the zirconating agent, borate and complexing agent in a mass ratio of (2-6):(1-4):1 to obtain a zirconium-based conversion solution; Zirconization process: immersing the electrophoretic component in the zirconium-based conversion solution to form a zirconization film on the surface of the electrophoretic component.
[0005] According to any of the aforementioned embodiments of the present invention, the mass ratio of the zirconating agent, the borate and the complexing agent is (3-5):(2-3):1.
[0006] According to any of the aforementioned embodiments of the present invention, the mass concentration of the zirconating agent in the zirconium-based conversion solution is 0.8 g / L to 1.5 g / L.
[0007] According to any of the aforementioned embodiments of the present invention, the zirconating agent includes fluorozirconate and / or fluorozirconic acid.
[0008] According to any of the aforementioned embodiments of the present invention, the fluorozirconate includes at least one of potassium fluorozirconate, sodium fluorozirconate and ammonium fluorozirconate.
[0009] According to any of the aforementioned embodiments of the present invention, the fluorozirconate includes potassium fluorozirconate and sodium fluorozirconate, and the mass ratio of the potassium fluorozirconate to the sodium fluorozirconate is (3~5):1.
[0010] According to any of the foregoing embodiments of the present invention, the borate comprises at least one of sodium borate, potassium borate, potassium tetrafluoroborate and sodium tetrafluoroborate.
[0011] According to any of the aforementioned embodiments of the present invention, the complexing agent includes at least one of sodium citrate, sodium tartrate, sodium hexametaphosphate, sodium acetate, oxalic acid and sodium aminotricarboxylate.
[0012] According to any of the aforementioned embodiments of the present invention, the pH of the zirconium-based conversion solution is 4-5.
[0013] According to any of the aforementioned embodiments of the present invention, the electrophoretic element is immersed in the zirconium-based conversion solution for a period of 5 min to 20 min.
[0014] An embodiment of the present invention provides a coating method for an electrophoretic component, wherein a zirconizing agent, a borate, and a complexing agent are mixed in a mass ratio of (2-6): (1-4): 1 to obtain a zirconium-based conversion solution, and then the electrophoretic component is immersed in the above-mentioned zirconium-based conversion solution to form a zirconized film with a dense structure on the surface of the electrophoretic component, wherein the addition of the borate can help to form the film and increase the density of the film, so that the zirconized film can have a strong adhesion to the surface of the electrophoretic component, thereby reducing the shedding of the zirconized film, thereby helping the zirconized film to enhance the corrosion resistance and wear resistance of the electrophoretic component. Therefore, the coating method for an electrophoretic component provided by an embodiment of the present invention can form a zirconized film with a dense structure on the surface of the electrophoretic component, so that its adhesion to the surface of the electrophoretic component can be enhanced, thereby reducing the probability of the zirconized film shedding, thereby improving the corrosion resistance and wear resistance of the electrophoretic component.
[0015] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Various other advantages and benefits will become apparent to those skilled in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only used for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. In the accompanying drawings: Figure 1 A schematic flow chart of a coating method for an electrophoretic component provided in some embodiments of the present invention is shown. DETAILED DESCRIPTION
[0017] The above summary of the invention of the present invention is not intended to describe each disclosed embodiment or each implementation in the present invention. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, the enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0018] In this article, the electrophoretic part refers to a workpiece to be processed whose surface is coated with electrophoretic technology, wherein the workpiece to be processed can be a component for a vehicle or a metal component for other industrial fields.
[0019] See also Figure 1 As shown, an embodiment of the present invention provides a coating method for an electrophoretic element, and the coating method for an electrophoretic element includes: S100, a mixing step, mixing a zirconating agent, a borate and a complexing agent in a mass ratio of (2-6): (1-4): 1 to obtain a zirconium-based conversion solution; S200, zirconization process, immersing the electrophoretic component in a zirconium-based conversion solution to form a zirconization film on the surface of the electrophoretic component.
[0020] The coating method of the electrophoretic component provided in the embodiment of the present invention is to obtain a zirconium-based conversion solution by mixing a zirconizing agent, a borate and a complexing agent in a mass ratio of (2~6): (1~4): 1, and then immersing the electrophoretic component in the above-mentioned zirconium-based conversion solution to form a zirconized film with a dense structure on the surface of the electrophoretic component, wherein the addition of the borate can help to form the film and increase the density of the film, so that the adhesion between the zirconized film and the surface of the electrophoretic component is strong, and the zirconized film falls off less, thereby helping the zirconized film to enhance the corrosion resistance and wear resistance of the electrophoretic component. Therefore, the coating method of the electrophoretic component provided in the embodiment of the present invention can form a zirconized film with a dense structure on the surface of the electrophoretic component, so that its adhesion to the surface of the electrophoretic component can be enhanced, and the probability of the zirconized film falling off can be reduced, thereby improving the corrosion resistance and wear resistance of the electrophoretic component.
[0021] In some possible embodiments of the present invention, the mass ratio of the zirconating agent, borate and complexing agent is (3-5): (2-3): 1. When the mass ratio of the zirconating agent, borate and complexing agent is within the above range, they can better cooperate with each other to further improve the compactness of the zirconization film and reduce the occurrence of its shedding, thereby further improving the anti-corrosion and wear resistance of the electrophoretic part.
[0022] For example, the mass ratio of the zirconating agent, the borate and the complexing agent may be, but is not limited to, 2:1:1, 2:2:1, 3:2:1, 3:3:1, etc.
[0023] Furthermore, in the zirconium-based conversion solution, selecting appropriate components and their contents can help form a zirconium film with a dense structure and enhance the adhesion between the zirconium film and the surface of the electrophoretic component to improve the corrosion resistance and wear resistance of the electrophoretic component.
[0024] In some possible embodiments of the present invention, the mass concentration of the zirconizing agent in the zirconium-based conversion solution is 0.8 g / L to 1.5 g / L. The mass concentration of the zirconizing agent within the above range can increase the formation rate of zirconium oxide and the modulus of the zirconized film, thereby helping to form a dense structure of the zirconized film to improve the corrosion resistance and wear resistance of the electrophoretic part.
[0025] Illustratively, the mass concentration of the zirconizing agent in the zirconium-based conversion liquid can be, but is not limited to, 0.8 g / L, 0.81 g / L, 0.82 g / L, 0.83 g / L, 0.84 g / L, 0.85 g / L, 0.86 g / L, 0.87 g / L, 0.88 g / L, 0.89 g / L, 0.9 g / L, 0.91 g / L, 0.92 g / L, 0.93 g / L, 0.94 g / L, 0.95 g / L, 0.96 g / L, 0.97 g / L, 0.98 g / L, 0.99 g / L, 1 g / L, 1.1 g / L, 1.2 g / L, 1.3 g / L, 1.4 g / L, 1.5 g / L or a range consisting of any two of the above values.
[0026] In some possible embodiments of the present invention, in the coating process, the pH of the chemical conversion solution is 4 to 5. When the pH of the chemical conversion solution is within the above range, the amount of zirconium film formed can be increased, thereby helping to form a dense structure of the zirconium film to improve the corrosion resistance and wear resistance of the electrophoretic part.
[0027] Illustratively, the pH of the chemical conversion solution may be, but is not limited to, 4, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5, or a range consisting of any two of the above values.
[0028] In some possible embodiments of the present invention, the zirconating agent includes fluorozirconate and / or fluorozirconic acid.
[0029] In some possible embodiments of the present invention, the fluorozirconate includes at least one of potassium fluorozirconate, sodium fluorozirconate and ammonium fluorozirconate.
[0030] In some possible embodiments of the present invention, the fluorozirconate includes potassium fluorozirconate and sodium fluorozirconate, and the mass ratio of potassium fluorozirconate to sodium fluorozirconate is (3-5): 1. The above zirconizing agent contains different cations, which can repel each other to reduce the occurrence of agglomeration, thereby helping to form zirconium oxide particles with smaller particle size and further improve the density of the zirconized film.
[0031] In some possible embodiments of the present invention, the borate includes at least one of sodium borate, potassium borate, potassium tetrafluoroborate and sodium tetrafluoroborate.
[0032] In some possible embodiments of the present invention, the complexing agent includes at least one of sodium citrate, sodium tartrate, sodium hexametaphosphate, sodium acetate, oxalic acid and sodium aminotricarboxylate.
[0033] In an embodiment of the present invention, the pH of the zirconium-based conversion solution can be adjusted by adding an acid solution, such as acetic acid, phosphoric acid, etc.
[0034] In addition, in some possible embodiments of the present invention, the electrophoretic element is immersed in the zirconium-based conversion solution for 5 minutes to 20 minutes. When the electrophoretic element is immersed in the zirconium-based conversion solution for a time within the above range, it can help to form a zirconium film of appropriate thickness and enhance the adhesion between the zirconium film and the electrophoretic element to improve the corrosion resistance and wear resistance of the electrophoretic element.
[0035] In the above-mentioned embodiments, the electrophoretic member is generally a metal plate for vehicles, such as a cold-rolled plate.
[0036] The following embodiments describe the disclosure of the present invention in more detail, and these embodiments are only for illustrative purposes, because it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present invention. Unless otherwise stated, all parts, percentages and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized according to conventional methods, and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0037] Example 1 This embodiment provides a coating method for an electrophoretic element, comprising: The cold-rolled sheet is immersed in a zirconium-based conversion solution for 10 minutes to form a zirconium film on the surface of the electrophoretic part, wherein the pH of the zirconium-based conversion solution is 4, and the zirconium-based conversion solution includes potassium fluorozirconate, potassium borate, acetic acid and sodium citrate, the mass concentration of potassium fluorozirconate in the zirconium-based conversion solution is 0.6 g / L, the mass concentration of potassium borate in the zirconium-based conversion solution is 0.4 g / L, and the mass concentration of sodium citrate in the zirconium-based conversion solution is 0.2 g / L.
[0038] Example 2 This embodiment provides a coating method for an electrophoretic element, comprising: The cold-rolled sheet is immersed in a zirconium-based conversion solution for 10 minutes to form a zirconium film on the surface of the electrophoretic part, wherein the pH of the zirconium-based conversion solution is 4, and the zirconium-based conversion solution includes potassium fluorozirconate, potassium borate, acetic acid and sodium citrate, the mass concentration of potassium fluorozirconate in the zirconium-based conversion solution is 0.8 g / L, the mass concentration of potassium borate in the zirconium-based conversion solution is 0.4 g / L, and the mass concentration of sodium citrate in the zirconium-based conversion solution is 0.2 g / L.
[0039] Example 3 This embodiment provides a coating method for an electrophoretic element, comprising: The cold-rolled sheet is immersed in a zirconium-based conversion solution for 10 minutes to form a zirconium film on the surface of the electrophoretic part, wherein the pH of the zirconium-based conversion solution is 4, and the zirconium-based conversion solution includes potassium fluorozirconate, potassium borate, acetic acid and sodium citrate, the mass concentration of potassium fluorozirconate in the zirconium-based conversion solution is 0.8 g / L, the mass concentration of potassium borate in the zirconium-based conversion solution is 0.2 g / L, and the mass concentration of sodium citrate in the zirconium-based conversion solution is 0.2 g / L.
[0040] Example 4 This embodiment provides a coating method for an electrophoretic element, comprising: The cold-rolled sheet is immersed in a zirconium-based conversion solution for 10 minutes to form a zirconium film on the surface of the electrophoretic part, wherein the pH of the zirconium-based conversion solution is 4, and the zirconium-based conversion solution includes potassium fluorozirconate, potassium borate, acetic acid and sodium citrate, the mass concentration of potassium fluorozirconate in the zirconium-based conversion solution is 0.9 g / L, the mass concentration of potassium borate in the zirconium-based conversion solution is 0.6 g / L, and the mass concentration of sodium citrate in the zirconium-based conversion solution is 0.3 g / L.
[0041] Example 5 This embodiment provides a coating method for an electrophoretic element, comprising: The cold-rolled sheet is immersed in a zirconium-based conversion solution for 10 minutes to form a zirconium film on the surface of the electrophoretic part, wherein the pH of the zirconium-based conversion solution is 4, and the zirconium-based conversion solution includes potassium fluorozirconate, potassium borate, acetic acid and sodium citrate, the mass concentration of potassium fluorozirconate in the zirconium-based conversion solution is 1.2 g / L, the mass concentration of potassium borate in the zirconium-based conversion solution is 0.4 g / L, and the mass concentration of sodium citrate in the zirconium-based conversion solution is 0.2 g / L.
[0042] Example 6 This embodiment provides a coating method for an electrophoretic element, comprising: The cold-rolled sheet is immersed in a zirconium-based conversion solution for 10 minutes to form a zirconium film on the surface of the electrophoretic part, wherein the pH of the zirconium-based conversion solution is 4, and the zirconium-based conversion solution includes potassium fluorozirconate, potassium borate, acetic acid and sodium citrate, the mass concentration of potassium fluorozirconate in the zirconium-based conversion solution is 1.5 g / L, the mass concentration of potassium borate in the zirconium-based conversion solution is 0.3 g / L, and the mass concentration of sodium citrate in the zirconium-based conversion solution is 0.3 g / L.
[0043] Example 7 This embodiment provides a coating method for an electrophoretic element, comprising: The cold-rolled sheet is immersed in a zirconium-based conversion solution for 10 minutes to form a zirconium film on the surface of the electrophoretic part, wherein the pH of the zirconium-based conversion solution is 4, and the zirconium-based conversion solution includes sodium fluorozirconate, potassium borate, acetic acid and sodium citrate, the mass concentration of sodium fluorozirconate in the zirconium-based conversion solution is 1.5 g / L, the mass concentration of potassium borate in the zirconium-based conversion solution is 0.3 g / L, and the mass concentration of sodium citrate in the zirconium-based conversion solution is 0.3 g / L.
[0044] Example 8 This embodiment provides a coating method for an electrophoretic element, comprising: The cold-rolled sheet is immersed in a zirconium-based conversion solution for 10 minutes to form a zirconium film on the surface of the electrophoretic part, wherein the pH of the zirconium-based conversion solution is 4, and the zirconium-based conversion solution includes potassium fluorozirconate, sodium fluorozirconate, potassium borate, acetic acid and sodium citrate, the mass concentration of potassium fluorozirconate in the zirconium-based conversion solution is 1.2 g / L, the mass concentration of sodium fluorozirconate in the zirconium-based conversion solution is 0.3 g / L, the mass concentration of potassium borate in the zirconium-based conversion solution is 0.3 g / L, and the mass concentration of sodium citrate in the zirconium-based conversion solution is 0.3 g / L.
[0045] Example 9 This embodiment provides a coating method for an electrophoretic element, comprising: The cold-rolled sheet is immersed in a zirconium-based conversion solution for 10 minutes to form a zirconium film on the surface of the electrophoretic part, wherein the pH of the zirconium-based conversion solution is 4, and the zirconium-based conversion solution includes potassium fluorozirconate, sodium fluorozirconate, potassium borate, acetic acid and sodium citrate, the mass concentration of potassium fluorozirconate in the zirconium-based conversion solution is 1.25 g / L, the mass concentration of sodium fluorozirconate in the zirconium-based conversion solution is 0.25 g / L, the mass concentration of potassium borate in the zirconium-based conversion solution is 0.3 g / L, and the mass concentration of sodium citrate in the zirconium-based conversion solution is 0.3 g / L.
[0046] Example 10 This embodiment provides a coating method for an electrophoretic element, comprising: The cold-rolled sheet is immersed in a zirconium-based conversion solution for 10 minutes to form a zirconium film on the surface of the electrophoretic part, wherein the pH of the zirconium-based conversion solution is 4, and the zirconium-based conversion solution includes potassium fluorozirconate, sodium fluorozirconate, potassium tetrafluoroborate, acetic acid and sodium citrate, the mass concentration of potassium fluorozirconate in the zirconium-based conversion solution is 1.25 g / L, the mass concentration of sodium fluorozirconate in the zirconium-based conversion solution is 0.25 g / L, the mass concentration of potassium tetrafluoroborate in the zirconium-based conversion solution is 0.3 g / L, and the mass concentration of sodium citrate in the zirconium-based conversion solution is 0.3 g / L.
[0047] Embodiment 11 This embodiment provides a coating method for an electrophoretic element, comprising: The cold-rolled sheet is immersed in a zirconium-based conversion solution for 10 minutes to form a zirconium film on the surface of the electrophoretic part, wherein the pH of the zirconium-based conversion solution is 4, and the zirconium-based conversion solution includes potassium fluorozirconate, sodium fluorozirconate, potassium tetrafluoroborate, potassium borate, acetic acid and sodium citrate, the mass concentration of potassium fluorozirconate in the zirconium-based conversion solution is 1.25 g / L, the mass concentration of sodium fluorozirconate in the zirconium-based conversion solution is 0.25 g / L, the mass concentration of potassium tetrafluoroborate in the zirconium-based conversion solution is 0.2 g / L, the mass concentration of potassium borate in the zirconium-based conversion solution is 0.1 g / L, and the mass concentration of sodium citrate in the zirconium-based conversion solution is 0.3 g / L.
[0048] Comparative Example 1 This comparative example provides a coating method for an electrophoretic component, comprising: The cold-rolled sheet is immersed in a zirconium-based conversion solution for 10 minutes to form a zirconium film on the surface of the electrophoretic part, wherein the pH of the zirconium-based conversion solution is 4, and the zirconium-based conversion solution includes potassium fluorozirconate, acetic acid and sodium citrate, the mass concentration of potassium fluorozirconate in the zirconium-based conversion solution is 0.8 g / L, and the mass concentration of sodium citrate in the zirconium-based conversion solution is 0.2 g / L.
[0049] Comparative Example 2 This comparative example provides a coating method for an electrophoretic component, comprising: The cold-rolled sheet is immersed in a zirconium-based conversion solution for 10 minutes to form a zirconium film on the surface of the electrophoretic part, wherein the pH of the zirconium-based conversion solution is 4, and the zirconium-based conversion solution includes potassium fluorozirconate, potassium borate, acetic acid and sodium citrate, the mass concentration of potassium fluorozirconate in the zirconium-based conversion solution is 0.7 g / L, the mass concentration of potassium borate in the zirconium-based conversion solution is 0.1 g / L, and the mass concentration of sodium citrate in the zirconium-based conversion solution is 0.1 g / L.
[0050] Test Section 1) Zirconium oxide particle size test in zirconium film The particle size of zirconium oxide in the zirconium film was detected using a nanoparticle tracking analyzer.
[0051] 2) Porosity test The porosity of the zirconium film was tested according to the standard "GB / T24586-2009 Determination of Apparent Density, True Density and Porosity of Iron Ore", and the test gas was helium. The test results are shown in Table 1. The smaller the porosity, the denser the structure of the zirconium film.
[0052] 3) Adhesion test The adhesion of the coating is measured according to GB / T 9286 standard. The specific method is as follows: Use an NT knife to draw 6*6 lines (25 1mm2 squares) on the surface of the coated aluminum part, and keep the test surface as flat as possible. Stick the tape (tape viscosity is greater than or equal to 5.3N) to the surface of the sample, and compact the tape with a rubber to make the tape fully contact with the test surface, and let it stand for 3 minutes. Quickly tear off the tape in a 90-degree direction, visually inspect the test surface, and refer to the ISO standard rating.
[0053] ISO Standard Rating: Grade 0: 5B, the edges of the cut are completely smooth, and there is no peeling on the edges of the lattice.
[0054] Level 1: 4B, there is a small piece of peeling at the intersection of the cuts, and the actual damage in the grid area is less than or equal to 5%.
[0055] Level 2: 3B, there is peeling at the edge or intersection of the incision, and the area is 5%-15%.
[0056] Level 3: 2B, there is partial peeling or large-scale peeling along the edge of the incision, or part of the grid is peeled off in one piece, and the peeling area is 15%-35%.
[0057] Level 4: 1B, the cut edge is larger than peeling or some squares are partially or completely peeled off, with an area of 35%-65%.
[0058] Level 5: 0B, there are pieces of paint falling off at the edges and intersections of the lines, and the total falling area is greater than 65%.
[0059] 4) Anti-corrosion performance test The test was carried out in accordance with the national standard GB / T 2423.17-2008, wherein the salt water concentration was 5%, the temperature in the salt spray chamber was controlled at 35°C~37°C, the salt spray test time was 450h, and after the salt spray test, the surface of the cold-rolled sheet was observed for rust.
[0060] 5) Wear resistance test The wear resistance was tested using the UMT friction and wear test system. The specific method is as follows: a linear reciprocating friction and wear test was performed in the middle of the zirconized film of the cold-rolled plate along the width direction. The relevant test parameters are as follows: the ball is GCr15 steel with a diameter of 3 mm, the friction speed is 20 mm / s, the load is 6 N, and the test time is 15 min. The test results are shown in Table 1. The smaller the wear scar width and wear scar depth, the better the wear resistance.
[0061] Table 1 Test results of Examples 1-11 and Comparative Examples 1-2
[0062] According to Table 1, by comparing the test results of Examples 1-11 and Comparative Examples 1-2, it can be seen that in the coating method of the electrophoretic component provided by the present invention, the zirconizing agent, the borate and the complexing agent are mixed in a mass ratio of (2-6): (1-4): 1 to obtain a zirconium-based conversion liquid, which can reduce the particle size of the formed zirconium oxide, and the zirconized film has good compactness, that is, the porosity is small, so that the formed zirconized film has strong adhesion to the surface of the electrophoretic component, thereby improving the corrosion resistance and wear resistance of the electrophoretic component.
[0063] From the comparison of the test results of Examples 1 to 11 and Comparative Example 1, it can be seen that no borate is added in Comparative Example 1, resulting in an increase in the porosity of the zirconium oxide film formed therein and an increase in the particle size of zirconium oxide in the film, which in turn reduces its adhesion to the electrophoretic component, causing the zirconium oxide film to fall off easily, and the corrosion resistance and wear resistance of the electrophoretic component are far inferior to those of Examples 1 to 11.
[0064] From the test results of Examples 1 to 11 and Comparative Example 2, it can be seen that the mass ratio of the zirconizing agent, borate and complexing agent in Comparative Example 2 is not set within the range of (2 to 6): (1 to 4): 1, which results in an increase in the porosity of the zirconized film formed therein and an increase in the particle size of zirconium oxide in the film, thereby reducing its adhesion to the electrophoretic component, causing the zirconized film to fall off easily, and the corrosion resistance and wear resistance of the electrophoretic component are far inferior to those of Examples 1 to 11.
[0065] From the test results of Examples 1 and 2 to 11, it can be seen that the mass concentration of the zirconizing agent in the zirconium-based conversion solution is in the range of 0.8 g / L to 1.5 g / L, which can help form zirconium oxide with smaller particle size and a zirconization film with good density, thereby enhancing the adhesion between the zirconization film and the electrophoretic part, thereby improving the corrosion resistance and wear resistance of the electrophoretic part.
[0066] Comparing the tests of Examples 2 and 4 with those of Examples 3, 5 and 6, it can be seen that when the mass ratio of the zirconating agent, the borate and the complexing agent is in the range of (3-5): (2-3): 1, zirconium oxide with a smaller particle size and a zirconization film with good density can be formed.
[0067] Comparing the test results of Examples 6, 7, 8 and 9, it can be seen that adding two or more zirconizing agents with a mass ratio in the range of (3-5):1 can help form zirconium oxide with smaller particle size and a zirconized film with good density.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention. In particular, as long as there is no structural conflict, the various technical features mentioned in each embodiment can be combined in any way. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A coating method for an electrophoretic component, characterized in that: The coating method of the electrophoretic element comprises: Mixing step: mixing the zirconating agent, borate and complexing agent in a mass ratio of (2-6):(1-4):1 to obtain a zirconium-based conversion solution; Zirconization process: immersing the electrophoretic component in the zirconium-based conversion solution to form a zirconization film on the surface of the electrophoretic component.
2. The electrophoretic coating method according to claim 1, characterized in that: The mass ratio of the zirconating agent, the borate and the complexing agent is (3-5):(2-3):
1.
3. The coating method of an electrophoretic element according to claim 1, characterized in that: The mass concentration of the zirconating agent in the zirconium-based conversion solution is 0.8 g / L to 1.5 g / L.
4. The coating method of an electrophoretic element according to claim 1, characterized in that: The zirconating agent includes fluorozirconate and / or fluorozirconic acid.
5. The coating method of an electrophoretic element according to claim 4, characterized in that: The fluorozirconate includes at least one of potassium fluorozirconate, sodium fluorozirconate and ammonium fluorozirconate.
6. The coating method of an electrophoretic element according to claim 5, characterized in that: The fluorozirconate includes potassium fluorozirconate and sodium fluorozirconate, and the mass ratio of the potassium fluorozirconate to the sodium fluorozirconate is (3~5):
1.
7. The coating method of an electrophoretic element according to claim 1, characterized in that: The borate includes at least one of sodium borate, potassium borate, potassium tetrafluoroborate and sodium tetrafluoroborate.
8. The coating method of an electrophoretic element according to claim 1, characterized in that: The complexing agent includes at least one of sodium citrate, sodium tartrate, sodium hexametaphosphate, sodium acetate, oxalic acid and sodium aminotricarboxylate.
9. The coating method of an electrophoretic element according to claim 1, characterized in that: The pH of the zirconium-based conversion solution is 4-5.
10. The coating method of an electrophoretic element according to claim 1, characterized in that: The electrophoretic element is immersed in the zirconium-based conversion solution for 5 minutes to 20 minutes.
Citation Information
Patent Citations
Weakly acidic non-phosphorus transforming agent
CN103710688A
Ceramic agent for hot galvanized plate and preparation method of ceramic agent
CN103952688A
Non-phosphorus converting agent and using method thereof
CN106544662A
Modified zirconium-based conversion film used for metal surface treatment and preparing method and application thereof
CN111593335A